Trend of measles in Turkey: a retrospective secondary data analysis - Turgut Sahinoz; Saime Sahinoz; Nahsan Kaya (Journal of the Pakistan Medical Association, 2021)
Objective: This study has been planned to analyze surveillance data of measles disease, to evaluate the trend, to make epidemiological evaluations about outbreaks and to help form national policies in the future. Methods: This study; covers a total of 1,050,567 measles cases reported to the Ministry of Health between 1960 and 2019 and published in the statistical annuals. It is a retrospective secondary data analysis. Results: In our study official measles data in 60-year period between the years 1960-2019 of Turkey Ministry of Health was analyzed and a total of 1,050,567 cases of measles was reported, the average number of cases of measles per year was 17.509, the average incidence rate over the 60-year period was 32.03 per hundred thousand and it was determined that the number of cases increased in some years above expectations. These increase years evaluated as epidemic were; 1965, 1969, 1973, 1975, 1981, 1983, 1989, 1993, 1996, 1998, 2001,2004, 2011-2013, 2017-2019 respectively. With the onset of vaccination in the following year of 1969, the peak of incidence (1970), the incidence rate decreased by about 27/100000. It was found that the incidence rate of measles decreased by 62% compared to pre-vaccination after a single dose of vaccine, and approximately 80% after the vaccination of the Extended Immunization Program (EIP). In our study a negative strong relation between MCV1 vaccination rates and number of measles cases (at one year later) has been found. Continuous...